Função logarítmicas e aplicações - LÔBO, Suelma do Nascimento Brito (2018)
In this work the development of Logarithmic Functions with applications is presented. Definitions of real numbers, functions and sequences are given for the development of the theme. It is characterized the Logarithmic Function and its properties, followed by the geometric definition of logarithms and the presentation of base e, formalizing the definition of the natural logarithm. Justifying the research, applications are developed in several areas, emphasizing the necessity and importance of the logarithmic functions.